Severe peptic oesophagitis. Issue 10 (October 1969) - Brunnen, P. L.; Karmody, A. M.; Needham, C. D.
Abstract : The incidence, clinical and investigative features, treatment, and course of severe oesophagitis in 200 patients seen and followed up in the Thoracic Surgical Department for north east Scotland from 1951 to 1967 are reviewed. The male/female ratio was 1/1·9. The incidence of severe oesophagitis (grades III and IV) approximated to 4·5 per 100, 000; there was a dramatic increase from the age of 50 years onwards. Reflux, with or without hiatal hernia, precedes oesophagitis and has an incidence in excess of 86 per 100, 000. It is difficult to assess the extent to which reflux produces mild oesophagitis, but it is clear that it only infrequently leads to the severe grades. Severe oesophagitis does not always need operative treatment. A conservative regime, supplemented by bouginage as required, enables the poorer-risk older patient to live a near-normal life span, in very reasonable comfort. Fifty-three patients of the whole series were operated upon, half primarily and half after previous conservative treatment. The problems of operative treatment are discussed. Newer procedures designed to prevent reflux now allow operation to be more freely advised. Perhaps, rather surprisingly, severe oesophagitis had very little effect on the expectation of life, whether treatment was conservative or operative.